2021
DOI: 10.1186/s12909-021-02511-3
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of burnout-depression symptoms among Chinese neurology graduate students in a national cross-sectional study

Abstract: Background The overlap of burnout and depression is a phenomenon that can effectively reflect the psychological state of a group. However, whether burnout is a type of depression is still debated in current research. The high incidence of burnout and depressive symptoms among medical students indicates that it is urgent to provide appropriate health services for them. However, the proportion of burnout and depression in the overlapping symptoms experienced by medical students, and the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
8
0
2
Order By: Relevance
“…A study on health workers demonstrated that depression has an indirect effect on the dimensions of burnout, which are partially mediated by resilience ( 29 ). An overlap between depressive symptoms and burnout has also been suggested ( 30 ), and burnout has been considered a precursor of depression ( 31 ). Other researchers have emphasized that there are obvious differences between burnout and psychological distress ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study on health workers demonstrated that depression has an indirect effect on the dimensions of burnout, which are partially mediated by resilience ( 29 ). An overlap between depressive symptoms and burnout has also been suggested ( 30 ), and burnout has been considered a precursor of depression ( 31 ). Other researchers have emphasized that there are obvious differences between burnout and psychological distress ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have focused on career-choice regret among healthcare professionals and medical students, most have not been in the context of the COVID-19 outbreak ( 8 , 11 13 ). Only one study investigated the impact of COVID-19 outbreak on the career preferences of medical students in China ( 7 ), focusing only on a particular specialty but not on a broader range of doctors,nurses and medical students who are potential doctors or nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also found that work-related risk factors for job burnout were predictors of depression ( 64 ). Furthermore, a study of Chinese neurology postgraduates demonstrated an overlap between job burnout and depressive symptoms ( 10 ). Job burnout, career choice regret, and depressive symptoms may overlap because depressive symptoms are the risk factor with the highest odds ratio for job burnout and career choice regret, and job burnout and career choice regret are also the risk factor with the highest odds ratio for depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that regret induced a more intense dislike of the outcome of the career choice, which could increase the risk of burnout ( 9 ). Furthermore, career choice regret has been associated with depressive symptoms ( 10 ). Research shows that experiencing regret is related to an increase in depressive tendencies, the explanation being that regret plays a partial mediation role between other variables and depression ( 11 ).…”
Section: Introductionmentioning
confidence: 99%